Comparative Studies of Fatty Acid Methyl, Ethyl and i-Propyl Esters of Tamarindus indica Seed Oil as Biodiesel Base-Stock - Rajak, Amit Kumar; Karuna M.S.L.; Deverapaga, Madhu; Vidavalur, Siddaiah; Padmaja, Korlipara V. (Asian Publication Corporation, 2023)
The unsaturated fatty acids found in tamarind seed oil include oleic acid (16.0%), linoleic acid (56.0%), palmitic acid (8.0%) and stearic acid (4.0%). The free fatty acids (0.6%) present in the tamarind seed oil was converted to methyl, ethyl and isopropyl esters. Further, the base stocks were prepared by employing transesterification reaction catalyzed by a base. Biodiesel fuels thus prepared were evaluated for different parameters and methyl esters were found to show ester content (97.3%), density (0.86315 g/cm3), acid value (0.42), oxidation stability (1.49 h), flash point (137.2 °C) and kinematic viscosity (5.09 cSt), ethyl esters have shown a kinematic viscosity (5.54 cSt), density (0.87030 g/cm3), acid value (0.45), oxidation stability (2.16 h), flash point (141.2 °C), ester content (97.7%) and isopropyl esters exhibited kinematic viscosity (20.05 cSt), density (0.9220 g/cm3), acid value (0.58), oxidation stability (0.05 h) and flash point (145.3 °C). The study involved investigation of effectiveness of four different antioxidants namely, butylated hydroxyl toluene (BHT), butylated hydroxyl anisole (BHA), t-butyl hydroxyl quinone (TBHQ) and diphenylamine (DPA) in different concentrations to the prepared methyl and ethyl biodiesels. BHA and BHT were observed to exhibit enhanced oxidation stability of produced biodiesel. The physical and chemical properties of methyl and ethyl esters were found to lie within EN and ASTM specifications.
This paper published with affiliation IIT (BHU) Varanasi in Open Access Mode.
Keywords: Antioxidant; Biodiesel; Oxidative stability; Tamarindus indica oil